ALT-C, a disintegrin-like Cys-rich protein from Bothrops alternatus, increases skeletal myoblast viability - Mesquita-Ferrari,RA (2009)
ALT-C, an ECD motif (glutamic acid, cysteine, aspartic acid) disintegrin from Bothrops alternatus snake venom, induces α2β1 integrin-mediated signaling and neutrophil chemotaxis. In vitro, in human umbilical vein endothelial cells (HUVEC), ALT-C induces cell proliferation, thus showing an interesting potential for tissue regeneration studies. This work aimed to evaluate the influence of ALT-C in myoblast viability and differentiation. Myoblasts were obtained from hind limb muscles of 3 to 4-day old Wistar rats. The cells were incubated with ALT-C at different concentrations and incubation periods were followed by total RNA isolation. cDNA synthesis and real time polymerase chain reaction (PCR) were performed with primers of myoD as well as of both (slow and fast) myosin heavy chain isoforms (MHC). ECD-disintegrin increased myoblast viability in a dose-dependent way, mostly with 50 to 100 nM concentrations, and such effect was more prevalent after 48 hours. No changes in gene expression of both MHC isoforms were observed in ALT-C-treated cells. MyoD expression was not detected, which suggests that myoblasts were in mature stages. Protease activity and cytokine array tested in a medium of 50 nM ALT-C-treated cells after 48 hours were not different from controls. In conclusion, it was shown that myoblats are sensitive to ALT-C indicating an integrin-mediated intracellular signaling that increases cell viability.